2018
DOI: 10.3892/mmr.2018.9401
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Kr�ppel‑like factor 1 inhibits the metastasis and invasion of cervical cancer cells

Abstract: Cervical cancer is one of the most common malignancies that seriously threatens women's health. Krüppel-like factors (KLFs) have been reported to be associated with the progression of cervical cancer. The role of KLF1 in cervical cancer, which still remains unclear, was investigated in the present study. The expression of KLF1 was detected in different cervical cell lines by reverse transcription-quantitative polymerase chain reaction (RT-qPCR) and western blotting. Cell proliferation, metastasis and invasion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…It has been reported that the expression of KLF1 enhanced the proliferation, migration and invasion of cervical cancer cells [ 9 ]. Moreover, some study revealed that KLF1 promoted the proliferation and invasiveness of breast cancer cells by activating the EMT process [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the expression of KLF1 enhanced the proliferation, migration and invasion of cervical cancer cells [ 9 ]. Moreover, some study revealed that KLF1 promoted the proliferation and invasiveness of breast cancer cells by activating the EMT process [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, KLF1 is highly expressed in a variety of tumors, such as cervical cancer. The expression of KLF1 promoted the proliferation and EMT of cervical cancer cells by activating PI3K/Akt pathway [ 9 ]. KLF1 is also associated with drug resistance of ovarian cancer cells [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several other KLFs also participate in the regulation of PI3K/AKT signaling. KLF1 promotes metastasis and invasion via the PI3K/AKT signaling pathway in cervical cancer cells by enhancing the phosphorylation levels of PI3K and AKT ( 41 ). KLF10 inhibits melanoma cells’ proliferation, invasion, and migration by upregulating acyl−CoA medium−chain synthetase 3.…”
Section: Klfs-mediated Molecular Regulationmentioning
confidence: 99%
“…Downregulation of KLF1 can inhibit the invasion and migration ability of cervical cancer cells. 10 KLF3 shows a high expression trend in lung cancer patients, and reducing KLF3 expression can inhibit the growth and migration of lung cancer cells. 11 KLF16 also plays a role in tumor growth and metastasis.…”
Section: Introductionmentioning
confidence: 96%